Pemetaan Tingkat Kekeringan Lahan pada Fenomena El Nino 2002, 2009, dan 2015 di Provinsi Bali dengan Teknologi Penginderaan Jauh dan Sistem Informasi Geografis - KRISMAYANI, NI PUTU AYU; NUARSA, I WAYAN; SUYARTO, R. (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Mapping of Land Drought in El Nino Phenomenon 2002, 2009 and 2015 in Bali Province Using Remote Sensing Technology and Geographical Information System Land dryness caused by the El Nino phenomenon in an area has a major impact on land productivity. The objectives of this study are (1) to compare the level of land dryness based on the El Nino phenomenon in 2002, 2009 and 2015 ,  and (2) to determine the impact of El Nino on food crop production in Bali Province .  To achieve this goal, this study uses Terra MODIS images. Drought condition is evaluated using vegetation greenness and air temperature parameters. Normalized Difference Vegetation Index (NDVI) and Vegetation Condition Index (VCI) are used to predict the vegetation greenness, where as Land Surface Temperature (LST) and Temperature Condition Index (TCI) are utilized to estimate the air temperature. Finally, Vegetation Healthy Index (VHI) is calculated based on value of VCI and TCI. The results shows that the El Nino phenomena in 2002 is the strongest dryness in Bali Province followed by the El Nino in 2015 and 2009. Most of the drought is spread over coastal area of Bali Province. There is the time lag around 6 months between decreasing of rainfall and appearance of drought symptoms. The total production of food crops in 2015 is the lowest, namely 1,032,067 tons, compared with production in 2002 and 2009 that is 1,127,452 tons and 1,252,443 tons respectively. However, statistically El Nino phenomena has no significant effect on food crop production. This is caused by the rice field irrigation sistem in Bali Province is still well maintained and the ability of farmers to mitigate the impact of drough on agriculture production.